Study of cognitive functions in breast cancer patients: A case control study - Anupama Zeena Sequeira; K Krishnamurthy (Wolters Kluwer Medknow Publications, 2014)
Context: One-third of breast cancer survivors report difficulties with concentration, multi-tasking, and memory. Cognitive dysfunction can have an impact on quality of life by affecting activities of daily living, treatment compliance, interpersonal relationships, work/profession, and future. Aims: The objective of this study was to evaluate the cognitive functions in breast cancer patients. Settings and Design: This study was conducted in the outpatient department of Oncology from where the cases were recruited. The controls were patients attending other departments and not suffering from cancer. Materials and Methods: A total of 60 patients, 30 breast cancer patients and 30 non-cancer individuals patients matched for age, education were evaluated. Tools used were SMMSE, TMT-B, and DSST for evaluation of cognitive functions. Statistical Analysis: The various findings were analyzed using Chi-square test, Mann-Whitney Test, T test and ANOVA. Results: Breast cancer patients had highly statistically significant cognitive deficits in language and recall domains and significant deficit on orientation domain of SMMSE. They performed poorly in TMT-B, taking more time to complete the test which was statistically highly significant. No significant deficits were noted on the DSST test. Conclusion: Breast cancer patients show statistically significant cognitive deficits as compared to non cancer individuals.